Two Harvard economists on monetary economics: Lauchlin Currie and Hyman Minsky on financial systems and crises. Issue 3 (3rd July 2019) - Velasquez, Ivan D.
Abstract: In November 1987, Hyman Minsky visited Bogotá, Colombia, after being invited by a group of professors who at that time were interested in post Keynesian economics. There, Minsky delivered some lectures, and Lauchlin Currie attended two of those lectures at the National University of Colombia. Although Currie is not as well-known as Minsky in the American academy, both are outstanding figures in the development of non-orthodox approaches to monetary economics. Both alumni of the economics Ph.D. program at Harvard had a debate in Bogotá. Unfortunately, there are no formal records of this, so here a question arises: What could have been their respective positions? The aim of this article is to discuss Currie's and Minsky's perspectives on monetary economics and to speculate on what might have been said during their debate.